JURIDICAL ANALYSIS FOR LEGAL HOLDERS OF PROPERTY RIGHTS CERTIFICATES IN CASES OF OVERLAPPING OF LAND - Johannes Evan Budiman; Felix Furguson; Angie Angie (Sekolah Pascasarjana Universitas Swadaya Gunung Jati, 2023)
In living in society in modern times which are increasingly developing without limits, various kinds of inventions and innovations have touched everyday life, giving rise to various problems such as the right to own land. In regulating land ownership, the state must be present to overcome concerns about injustice in the acquisition and use of natural resources by the community. The state's actions in supervising the use of natural resources are carried out by issuing a number of statutory regulations, namely Law Number 6 of 1960 concerning the Principles of Agrarian Affairs. The aim of the research is to find out how to prevent land overlapping cases that occur in people's lives. The method used in this research is to use normative juridical research which is carried out by examining library materials or secondary materials. The conclusion of this study is that preventing land overlap is by improving the performance of good land administration, especially on land registration maps.